Bioplastic Prototype of Gayam Fruit and King Banana Skin with Glycerol Variation - Nur Alim Natsir; Asyik Nur Allifah AF (Jurnal Biologi Tropis, 2023)
Plastic is a popular packaging material used worldwide. Plastic has advantages such as being strong, light and elastic, but due to its slow decomposition process, its existence has an impact on the accumulation of plastic waste and the environment. Bioplastics made from Gayam starch and plantain peels with variations of glycerol are the best solutions to overcome the plastic problem because they are made from easily decomposed raw materials. The purpose of this study was to determine the bioplastic prototype of gayam fruit and plantain peel with glycerol variations. This type of research is quantitative with a laboratory experiment approach. This research was conducted on 24 February 2022 to 06 January 2023 at the Ambon IAIN MIPA Laboratory. Gayam fruit starch and plantain peel starch flour were made in a ratio of 1: 3. Then precipitated for 24 hours and dried in an oven for 4 hours at 50°C. Bioplastics are made by adding variations of glycerol 5%, 10%, 15%, and 20%. Bioplastic prototypes in the form of physical appearance, biodegradable tests and water resistance were analyzed descriptively using the ANOVA test (Analysis of Variance) and continued with Duncan's test to determine the significance of glycerol variations on bioplastic prototypes. The results showed that Gayam starch and plantain peel with variations in glycerol had a significant effect (P<0.05) on the bioplastic prototype.